Study on Tunnel Face Failure Mechanism in Two-Layer Soils - Nguyen, Tuan Anh; Nguyen, Minh Anh Trong (International Journal of Scientific Research in Civil Engineering, 2021)
Three-dimensional (3D) was not commonly used in the underground construction field as the stimulation process was quite complex and time-consuming. Recently, thanks to high precise calculator, the underground construction surveys by using 3D model gives more accurate results than that of 2D model. The reason is that 3D model represents not only all boundary conditions as theoretical models but also deformation area in two directions. Besides, it is possible for 3D model to analyse the tunnel stability and the balance pressure with the aim of ensuring the tunnel stability during the construction process. This article mentions the application of 3D finite element analysis on tunnel face failure mechanism and passive failure pressure in two-layer soils.
Keywords: FEM; Failure Mechanism; Passive Failure Pressure; Deformation; Tunnel Face